Cover Picture: A General Method for Growing Two‐Dimensional Crystals of Organic Semiconductors by "Solution Epitaxy" (Angew. Chem. Int. Ed. 33/2016). Issue 33 (6th June 2016) - Xu, Chunhui; He, Ping; Liu, Jie; Cui, Ajuan; Dong, Huanli; Zhen, Yonggang; Chen, Wei; Hu, Wenping
Abstract : Solution epitaxy is a method for growing high‐quality two‐dimensional crystals of organic semiconductors (2DCOS) up to centimeter size; these 2DCOS can be efficiently transferred to any substrate. In their Communication onpage 9519 ff., W. Hu and co‐workers show how this new method involves two steps: The self‐assembly of micrometer‐sized 2DCOS on the surface of water and their epitaxial growth into millimeter‐ or centimeter‐sized 2DCOS with a thickness of several molecular layers.